Exploring Electric Vehicle Purchase Intention in Jakarta: What Attracts Consumers? - Sapta Aji Yudistira; Daniel Tumpal Hamonangan Aruan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The transition to electric vehicles (EVs) is a global strategy aimed at reducing greenhouse gas emissions and mitigating the adverse effects of climate change, particularly in the transportation sector. This study seeks to analyze the factors influencing the purchase intention of EVs in Jakarta, a region with a low adoption rate despite various governmental incentives. Employing a combined framework of the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM), the research examines the influence of attitudes toward EVs, perceived usefulness, perceived risk, environmental concern, and subjective norms on purchase intention. Additionally, moderating variables such as monetary incentives, non-monetary incentives, and personal norms are evaluated to understand their role in strengthening or weakening the relationships between independent and dependent variables. Data were collected through a survey of 300 respondents in Jakarta and analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings aim to provide empirical insights to enrich the literature on environmentally friendly technology adoption and serve as a reference for policymakers and automotive industry stakeholders in formulating effective strategies to accelerate EVadoption in Indonesia.